Comparison of clinical profile of leptospirosis patients during post flood and non-post flood periods - ., Bhagyanath; Jacob, Jacob K.; Samuel, Suma; Kurup, Rakhi R.; Ravindran, Reshnu (International Journal of Research in Medical Sciences, 2021)
Background: Leptospirosis is a zoonotic infection with high mortality rates. The incidence of leptospirosis is more during floods. The aim of the study was to find the difference in clinical profile of leptospirosis during post flood and non-post flood periods. Methods: This was a cross sectional observational study comparing the clinical profile of leptospirosis patients admitted in Government Medical College Ernakulam, Kerala during the post flood period of 2018 with that of non-post flood period. The data with respect to clinical features and investigations were retrieved from the hospital records. Results: Out of the 42 patients studied 15 were from the post flood period and the rest 27 patients were from the non-post flood period. The mean age in the post flood group was 40 years and that in the non-post flood group 43 years. Myalgia, icterus and calf tenderness was significantly higher in the post flood group. The mean platelet count was significantly lower in the non-post flood period (p value=0.011). Mean serum urea and total bilirubin were significantly higher in the post flood group compared to non-post flood group (p value=0.001). Cardiac complications were seen only among the post flood group. Conclusions: The clinical profile and complications were different in leptospirosis patients during post flood and non-post flood periods. These findings help the treating physicians to formulate different approaches in treating patients during the post flood and non-post flood period.